Biology and population dynamics of brustooth lizardfish, saurida undosquamis (Richardson, 1848) along the Kerala coast - Nimisha, B. (KUFOS, 2018)
Abstract- The biology and population dynamics of the commercially important lizard fish (Saurida undosquamis) were studied along the Kerala coast. Gut content analysis revealed that fishes formed the primary food item with index value 64% followed by crustaceans 27% and cephalopods 9%. Cannibalism was noticed in both sexes with predominantly in male. Present study noticed a direct relationship of increasing trend of cannibalism with size. Actively or moderately fed fishes were more during post monsoon period. Gastro somatic index was found maximum during post monsoon and minimum during the monsoon period indicating an inverse relationship between feeding and spawning activity. The size at first maturity was estimated as 16.5 cm (Male) and 19 cm (Female). The species showed prolonged spawning period from August to February with a peak in August to December. The fecundity ranged from 20820(20cm, 103gm) and 72018 (30cm, 245gm). Ova diameter range 0.5µm to 0.9µm represented mature group. The overall sex ratio recorded was 1:1.23. Higher Gonado Somatic Index value observed during August to December for both male and female suggested spawning activity during this period. Less representation of mature individual in sample may be an indication that the species appears to breed away from the fishing ground. Length weight relationship was Male: W = 0.0233*L^ 3.1634 (r^2= 0.9064), Female: W =0.0144*L^ 3.2641 (r^2= 0.9397), Pooled:W= 0.0174*L^3.0092 (r^2 =0.9297). Von Bertalanffy growth constants were L∞=372.75, K= 0.82 and t0 = -0.042 respectively. Estimated mortality parameters was Z =1.78, M =0.78 and F = 1. The growth performance index was 4.95. The exploitation rate and ratio was 0.56 and 0.46 respectively. Results of the present study indicated that brushtooth lizardfish is overexploited along the Kerala coast.